A Symptom of Diplopia Demands Accommodative and Convergence Assessment Despite Advancing Age or Ocular Pathology - A Case Series. - Kalikivayi, Lavanya; Jacob, Sajeev Cherian; Kalikivayi, Venkataramana (Optometry & Visual Performance, 2022)
Background: Accommodation is stimulated by various factors, including probable size and distance of a stimulus, blur, spherical and chromatic aberrations, and continuous oscillations of the ciliary muscle tone. It is also influenced by spectacle or contact lenses wear. Two uncommon cases are reported with complaints of diplopia due to accommodative spasm as a result of uncorrected facultative hyperopia and convergence excess in a keratoconic patient due to contact lens wear. Case Reports: Case 1: A 58-year-old retired male presented with complaints of double vision both at distance and near. He was an extensive e-book reader. His best-corrected visual acuity improved to 6/6 and N6 in both eyes with spectacles, but the diplopia persisted. A homatropine refraction was performed, which revealed an uncorrected facultative hyperopic component leading to accommodative spasm. Upon full correction of the manifest hyperopia, the patient attained relief from accommodative spasm, and the diplopia resolved. Case 2: A 27-year-old male keratoconic patient whose vision was blurred with spectacles presented for an examination. His vision improved to 6/6 and N6 with Rose K contact lenses, but he developed diplopia at near with the contact lenses. Further examination revealed convergence excess. Consequently, he was prescribed +0.75 DS spectacles to be worn on top of his contact lenses for near and intermediate distance viewing, which relieved the diplopia. Conclusion: Diplopia has many causative factors, as seen by the two case reports presented. A full binocular vision workup including cycloplegic or dynamic refraction is warranted to help determine causation.